Transformasi Digital Komunitas Abrasea Indonesia untuk Penguatan Peran Konservasi Pesisir di Jawa Tengah - Sanusi, Ratna Nur Mustika; Ifriza, Yahya Nur; Febriyanto, Hendra (Informa Science, 2025)
Coastal abrasion in Central Java seriously threatens social, economic, and environmental sustainability. In response to this urgency, the Abrasea Indonesia Community was established as a new initiative for community-based conservation. However, as a newly formed organization, the effectiveness of its outreach programs and communication remains limited due to the absence of a structured digital platform. Therefore, this community service initiative aims to transform the community's operations by developing the digital platform abrasea.org as a hub for centralized information and increased public participation. The method employed is a participatory approach that actively involves community members in the planning and development of the platform, combined with quantitative and qualitative approaches to measure its success. The results show that within three months after its launch, the platform successfully increased website visitors by 75% and mobilized 80 new volunteers through online registration. This outcome strengthens institutional capacity and shifts the community's social behavior in organizing and publicizing activities. Thus, the digital platform has proven effective as a catalyst for expanding outreach and reinforcing the role of the Abrasea Indonesia Community in creating more sustainable conservation impacts since its inception.